“There is a strong visual component in radio”. Glenn Gould in conversation with John Thompson (Intermédialités / Intermediality, 2012)
The previously unpublished conversation presented here is taken from an unreleased video documentary, Radio as Music, which Gould produced in 1975. This document shows Gould explaining his programmatic vision of the specificities of radio musicality and also provides insight into the composer’s pioneering role as an intermedial artist using video techniques. The only section of the tape which was edited documents a studio session in which Gould and his collaborator, Donald Logan, are mixing the radio piece Quiet in the Land. Freelance producer John Thompson asks Gould a series of questions pertaining to the “contrapuntal radio documentary.” Radio as Music is a unique document, not only because Gould makes the conception process behind his composition technique explicit, but also because he comments on his production method by providing a greater understanding of its consequences in “musical” detail. (See “Radio as Music. A Video Document by [and with] Glenn Gould,” introduction by Philippe Despoix).